+0  
 
0
256
1
avatar

Please solve this for me..

Guest Dec 31, 2014

Best Answer 

 #1
avatar+87294 
+10

Here's (b)

x^2 + xy - y^2  = 1    using implicit differentiation, we have

2x + y + xy' - 2yy'  = 0

xy' - 2yy'  = -2x - y       multiply through by - 1 on both sides

2yy' - xy'  = 2x + y

y'(2y - x) = 2x + y

y' =  [2x + y ] /  [2y - x ]      and the slope of the tangent line at (2.3) is given by

y' = [2(2) + 3] / [2(3) - 2 ]   =   [7] / [ 6 - 2]  =  7 / 4  

Here's a graph of the tangent line to the "rotated" hyperbola at the point (2,3)....https://www.desmos.com/calculator/yuxxmj7ud9

Note, that the slope of the tangent line at this point = (7/4).....just as we expected...!!!

 

CPhill  Dec 31, 2014
 #1
avatar+87294 
+10
Best Answer

Here's (b)

x^2 + xy - y^2  = 1    using implicit differentiation, we have

2x + y + xy' - 2yy'  = 0

xy' - 2yy'  = -2x - y       multiply through by - 1 on both sides

2yy' - xy'  = 2x + y

y'(2y - x) = 2x + y

y' =  [2x + y ] /  [2y - x ]      and the slope of the tangent line at (2.3) is given by

y' = [2(2) + 3] / [2(3) - 2 ]   =   [7] / [ 6 - 2]  =  7 / 4  

Here's a graph of the tangent line to the "rotated" hyperbola at the point (2,3)....https://www.desmos.com/calculator/yuxxmj7ud9

Note, that the slope of the tangent line at this point = (7/4).....just as we expected...!!!

 

CPhill  Dec 31, 2014

13 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.